Approximation of Analytic Functions by Bessel's Functions of Fractional Order - Soon-Mo Jung (Abstract and Applied Analysis)
We will solve the inhomogeneous Bessel's differential equation x2y″(x)+xy′(x)+(x2-ν2)y(x)=∑m=0∞amxm, where ν is a positive nonintegral number and apply this result for approximating analytic functions of a special type by the Bessel functions of fractional order.